Updating the Antibacterial & Antiulcer Activity of Aegle Marmelos Linn - Tapan Kumar Mahato; Komal Sharma (Technological Innovation in Pharmaceutical Research Vol. 11, 2021)
Antimicrobial drugs are those drugs which are used to treat diseases caused by microorganisms. These disease causing microorganisms are called pathogenic microorganisms. To treat the diseases,antimicrobial medicines are used e.g. antibiotic, antiviral, antifungal and antiparasitic medicines. These microbes produces diseases not only in humans but in animals and plants too. Antimicrobial resistance (AMR) occurs when disease producing microbes gets resistant against the medications, so that the medications becomes ineffective which makes common infections difficult to treat and hence leads to increased risk of severe illness, disease spreading and death. According to the report of World Health Organization (WHO), the cases of AMR is continuously going upwards and it creates trouble in effective treatment and prevention of infections caused by microorganisms like bacteria, viruses, fungi and parasites. AMR makes the medicines ineffective so that the infections remains in the body and enhances the chances of spread to others. WHO recommends to minimize the use of synthetic antibiotics and to increase the use of herbal antimicrobial drugs. Using these recommended ways only, the AMR can be controlled or eliminated. Herbal drugs are considered to be therapeutically effective and free from side effects. In this chapter, a very potent herbal drug, Aegle Marmelos Linn. (Bael in hindi) has been discussed. Aegle marmelos Linn. is useful in treating many health ailments. Scientific studies reveals that It possess many pharmacological activities like anticonvulsant, antioxidant, antihyperglycemic, anxiolytic, antidepressant, antihistaminic, antimicrobial, hepatoprotective, analgesic, immune modulatory, cardio protective and antithyroid activity. Because of its antibacterial and antiulcer activity it is used to treat peptic ulcer patients. The bacteria which is responsible for peptic ulcer is Helicobacter pylori. This chapter discusses about the effect of Aegle Marmelos on bacterias including Helicobacter pylori.